In vitro activity of fosfomycin against bacterial pathogens isolated from urine specimens in Canada from 2007 to 2020: CANWARD surveillance study. (16th August 2022) - Karlowsky, James A; Baxter, Melanie R; Walkty, Andrew J; Lagacé-Wiens, Philippe R S; Bay, Denice; Adam, Heather J; Zhanel, George G
Abstract: Background: Multiple susceptible breakpoints are published to interpret fosfomycin MICs: ≤64 mg/L for Escherichia coli and Enterococcus faecalis grown from urine (CLSI M100); ≤32 mg/L for Enterobacterales and staphylococci when parenteral fosfomycin is prescribed (EUCAST); and ≤8 mg/L for uncomplicated urinary tract infection with E. coli when oral fosfomycin is used (EUCAST). Clinical laboratories are frequently requested to test fosfomycin against antimicrobial-resistant urinary isolates not included in standard documents. Methods: The in vitro activity of fosfomycin was determined using the CLSI agar dilution method for a 2007–20 collection of clinically significant Gram-negative (3656 Enterobacterales; 140 Pseudomonas aeruginosa ) and Gram-positive (346 E. faecalis ; 94 Staphylococcus aureus ) urinary isolates from the CANWARD surveillance study. Comparator agents were tested using CLSI broth microdilution. Results: Using the CLSI MIC breakpoint (≤64 mg/L), 99.2% of E. coli ( n =  2871; MIC90, 4 mg/L), including 96.7% of ESBL-positive isolates, were fosfomycin susceptible. Similarly, 95.8% of E. coli, including 95.2% of ESBL-positive isolates, were fosfomycin susceptible at ≤8 mg/L (EUCAST oral susceptible MIC breakpoint). All other species of Enterobacterales (except Citrobacter freundii ) and P. aeruginosa had higher fosfomycin MICs (MIC90 s, 64 to >512 mg/L) than E. coli . Using published breakpoints, 88.4% of E. faecalis (MIC ≤64 mg/L) and 97.9% of S. aureus (MIC ≤32 mg/L) isolates were fosfomycin susceptible. Conclusions: Fosfomycin demonstrated in vitro activity against frequently encountered Gram-positive and Gram-negative urinary pathogens; however, the extrapolation of current CLSI and EUCAST MIC breakpoints to pathogens not specified by standard methods requires further study and is currently not recommended.